Association between ambulatory skills and diffusion tensor imaging of corpus callosal white matter in infants with spina bifida. (1st November 2022) - Sanz Cortes, M.; Corroenne, R.; Sangi‐Haghpeykar, H.; Orman, G.; Shetty, A.; Castillo, J.; Castillo, H.; Johnson, R. M.; Shamshirsaz, A.; Belfort, M. A.; Whitehead, W.; Meoded, A.
Abstract: Objectives: To assess brain white matter using diffusion tensor imaging (DTI) at 1 year of age in infants diagnosed with open neural tube defect (ONTD) and explore the association of DTI parameters with ambulatory skills at 30 months of age. Methods: Magnetic resonance imaging (MRI) was performed at an average of 12 months of age and included an echo planar axial DTI sequence with diffusion gradients along 20 non‐collinear directions. TORTOISE software was used to correct DTI raw data for motion artifacts, and DtiStudio, DiffeoMap and RoiEditor were used for further postprocessing. DTI data were analyzed in terms of fractional anisotropy (FA), trace, radial diffusivity and axial diffusivity. These parameters reflect the integrity and maturation of white‐matter motor pathways. At 30 months of age, ambulation status was evaluated by a developmental pediatrician, and infants were classified as ambulatory if they were able to walk independently with or without orthoses or as non‐ambulatory if they could not. Linear mixed‐effects method was used to examine the association between study outcomes and study group. Possible confounders were sought, and analyses were adjusted for age at MRI scan and ventricular size by including them in the regression model as covariates. Results: Twenty patients with ONTD were included in this study, including three cases that underwent postnatal repair and 17 cases that underwent prenatal repair. There were five ambulatory and 15 non‐ambulatory infants evaluated at a mean age of 31.5 ± 5.7 months. MRI was performed at 50.3 (2–132.4) weeks postpartum. When DTI analysis results were compared between ambulatory and non‐ambulatory infants, significant differences were observed in the corpus callosum (CC). Compared with non‐ambulatory infants, ambulatory infants had increased FA in the splenium (0.62 (0.48–0.75) vs 0.41 (0.34–0.49); P  = 0.01, adjusted P  = 0.02), genu (0.64 (0.47–0.80) vs 0.47 (0.35–0.61); P  = 0.03, adjusted P  = 0.004) and body (0.55 (0.45–0.65) vs 0.40 (0.35–0.46), P  = 0.01, adjusted P  = 0.01). Reduced trace was observed in the CC of ambulatory children at the level of the splenium (0.0027 (0.0018–0.0037) vs 0.0039 (0.0034–0.0044) mm 2 /s; P  = 0.04, adjusted P  = 0.03) and genu (0.0029 (0.0020–0.0038) vs 0.0039 (0.0033–0.0045) mm 2 /s; P  = 0.04, adjusted P  = 0.01). In addition, radial diffusivity was reduced in the CC of the ambulatory children at the level of the splenium (0.00057 (0.00025–0.00089) vs 0.0010 (0.00084–0.00120) mm 2 /s; P  = 0.02, adjusted P  = 0.02) and the genu (0.00058 (0.00028–0.00088) vs 0.0010 (0.00085–0.00118) mm 2 /s; P  = 0.02, adjusted P  = 0.02). There were no differences in axial diffusivity between ambulatory and non‐ambulatory children. Conclusion: This study demonstrates a significant association between white matter integrity of connecting fibers of the corpus callosum, as assessed by DTI, and ambulatory skills at 30 months of age in infants with ONTD. © 2022 International Society of Ultrasound in Obstetrics and Gynecology.